Allele frequencies of STRs (F13A01, FESFPS and vWA) in random Chinese population of Malaysia - Maniam, Saravanakumar A/L
Biochemical and molecular genetic markers have played a vital role in forensic analysis of bio .. specimens and in kingships testing. However with the advent of DNA profiling technique positive identification has become a reality. The science of DNA profiling had revamped analytical procedures employed in the analysis. Short Tandem Repeats (STRs) DNA profiling is widely used in most of the laboratories for personal identification. A population database on the STR to be employed for analysis is a prerequisite. In the present study distribution of allele frequencies for three validated STRs - F13A01, FESFPS, vWA was compiled for the ethnic Chinese population of Malaysia. DNA samples form 100 random Chinese individual were processed using multiplex primer mix. There is no significant deviation from the Hardy-Weinberg equilibrium. The discrimination power of the three STRs is 0.9987.